Synergistic combination of pyrolysis, anaerobic digestion, and CHP plants. (February 2019) - Salman, Chaudhary Awais; Schwede, Sebastian; Naqvi, Muhammad; Thorin, Eva; Yan, Jinyue
Abstract: The anaerobic digestion of biodegradable fraction of municipal solid waste (MSW) is a widely used process for biogas production. However, the biodegradable fraction of MSW also contains lignocellulosic waste which hinders the biogas production if added to the digester in higher quantity. So it needs to be separated from biodegradable waste and sent for alternate treatment, e.g., incineration, landfilling or compositing. Pyrolysis of lignocellulosic waste to produce biochar, syngas, and bio oil is an alternate treatment to consider. Furthermore, there is a reported correlation between the addition of biochar in the digester and higher biogas production. Previously, we coupled the pyrolysis of lignocellulosic waste with anaerobic digestion plant. Pyrolysis produces the biochar and vapors. Biochar was added in the digester to enhance the biomethane production. The vapors produced in the pyrolysis process were converted to biomethane through the catalytic methanation process. The combination gives the overall efficiency of 67%. In this work, we modified the process concept to increase the integration level of these processes. The main issue with the pyrolysis process is its heat required to operate, while some of its downstream processes also generate excess heat. In this study, the pyrolysis of lignocellulosic waste is integrated with an operating combined heat and power (CHP) plant, by using its existing infrastructure for heat transport among different pyrolysis operations. The combustor of the CHP plant provides the heat for drying and pyrolysis while the excess heat is transferred back to the combustor. The biochar produced from pyrolysis is transported back to the digester as an adsorbent. The process simulation results show that the combined efficiency of pyrolysis with CHP plant reached 80%. If the biochar is sent back to the anaerobic digester, the synergetic efficiency of all three processes, i.e., pyrolysis-CHP and anaerobic digestion was obtained at 79.7% as compared with the 67% efficiency when the pyrolysis was only integrated with the anaerobic digestion process.